Spatio-temporal Fluctuation of Temperature Using Specific Climate Indices in South Xinjiang, China - Ahmad Ali Khan; Zhao Yuanjie; Jamil Khan; Rahman, Ghani; Muhammad Rafiq (Ecological Questions, 2023)
Temperature and precipitation are significant variables that can be used to determine the climatic variability in a region. This research study has focused on temperature, which is significant for the study of climatic variability over a long period in an area. The temperature has been assessed spatially and temporally in South Xinjiang, China using various climate indices. The temporal data about the temperature of seventeen meteorological stations were acquired from the Chinese Meteorology Administration (CMA) from 1980 to 2018. The Mann-Kendall (MK) trend test and Sen’s Slope (SS) statistical models were used to quantify the magnitude and temporal trend. The monthly and seasonal analysis of temperature reveals a significant increasing trend in mean maximum, mean minimum and average temperatures in the study area. The Sen’s Slope test results indicate an increasing monthly and seasonal temperature trend in almost all meteorological stations. The increasing trend in temperature is mainly due to the desert type of climate of the region that is gradually further aggravating with every passing year. This increasing temperature trend will smoothen the way for perpetual drought in the region in the future. Therefore, this research would be beneficial for future planning and management of water resources in the region and for making preventive measures to mitigate the impacts of climate change in the study area.